Liquid-phase electrical discharge plasmas with a silver electrode for inactivation of a pure culture of Escherichia coli in water. (December 2016) - Vukusic, Tomislava; Shi, Mengli; Herceg, Zoran; Rogers, Shane; Estifaee, Pooya; Thagard, Selma Mededovic
Abstract: This study investigates the possible application of direct-in-liquid electrical discharge plasmas for inactivation of Escherichia coli in water. Aqueous suspensions of pure cultures of Escherichia coli (ATCC 700891) were treated in a reactor that featured point-to-plate electrode configuration. The effects of the high voltage electrode material, plasma discharge frequency, and electrode polarity on inactivation rates were investigated. While it has been observed that all three selected parameters influence the effectiveness of the treatment, the choice of the high voltage electrode material appears to play the most important role. Silver is the most effective electrode material resulting in 6.5 log reduction in 60 s. To develop an understanding of the mechanistic action of silver on Escherichia coli and allow the further development of this technology for water disinfection purposes, control experiments with nanoparticle and ionic silver with and without plasma were performed. Highlights: Silver is an effective high voltage electrode material for direct-in-liquid plasma-assisted sterilization Negative polarity discharges achieve much higher inactivation rates than positive polarity discharges The contribution from silver to the overall inactivation rate is dominant compared to other physicochemical contributions